Multidisciplinary leadership training for undergraduate health science students may improve Ugandan healthcare - Najjuma, J N; Ruzaaza, G; Groves, S; Maling, S; Mugyenyi, G (African Journal of Health Professions Education, 2016)
Background. Community-based education research and service (COBERS) is a platform for embedding progressive transformative leadership and research-related medical education in Uganda. The leadership development programme (LDP) developed at Mbarara University of Science and Technology (MUST), Uganda is a key component of COBERS. Health science students at MUST are equipped by means of the LDP with leadership knowledge and skills, and a positive attitude towards leadership and rural communities. The programme involves employing interactive learner-centred education techniques, with the opportunity to implement these skills in a community setting immediately after the training. Objective. To assess the students’ self-reported perception and effectiveness of the pre-community placement LDP at MUST and its impact during the community clinical placement, and to measure the self-reported improvement of students’ knowledge and their application of leadership skills in the community. The results of the evaluation will improve and build on this educational programme. The study also evaluated the effectiveness of the preplacement leadership training course for undergraduates at MUST, as reported by students. Methods. The programme evaluation of the LDP used quantitative pretest and post-test measures and qualitative data from focus group discussions to enrich the evaluation. Data were collected from students before and after the 1-week leadership training course using the same self-administered questionnaire. Variables were then compared to evaluate the impact of the LDP. Results. Prior to the intervention, only 14% of the participants had ever attended a leadership training session. There was significant self-reported change in the task accomplishment skills, interpersonal relationship skills and quality of leadership. Conclusion. The results suggest that the LDP may increase leadership skills among health science students to improve healthcare in Uganda. Our study recommends that this leadership programme be considered for use by Ugandan medical training faculties and similar environments elsewhere
Keywords: Healthcare delivery; Uganda’s healthcare system; Community-based education research and service (COBERS); Health science students; Uganda